2009
DOI: 10.1889/jsid17.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Improved discharge characteristics using MgO single‐crystal particles and advanced CEL structure

Abstract: Abstract— Pioneer Corporation introduced plasma‐display‐panel (PDP) TVs in 2005, which achieved the highest dark‐room contrast ratio of 4000:1 at the time. These PDPs had a novel discharge cell structure consisting of a crystal emissive layer (CEL) on a MgO protective thin film. This cell structure is refered to as a CEL structure. Magnesium‐oxide single‐crystal particles, which have a unique luminance peak around 230–250 nm and a good exo‐electron‐emission property, were found to be an excellent material for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Such properties allow using this compound as a dielectric material to replace silicon dioxide in some applications [2]. MgO can also be used as a protective layer of plasma display panels to extend the service life of such panels through high durability and improved discharge characteristics [4][5][6]. Magnetic tunnel junctions (MTJ), where MgO is used as a barrier layer, are of great importance not only for the creation of microelectronic and spintronic devices but also to clarify the mechanisms of spin-dependent tunneling of electrons [7].…”
Section: Introductionmentioning
confidence: 99%
“…Such properties allow using this compound as a dielectric material to replace silicon dioxide in some applications [2]. MgO can also be used as a protective layer of plasma display panels to extend the service life of such panels through high durability and improved discharge characteristics [4][5][6]. Magnetic tunnel junctions (MTJ), where MgO is used as a barrier layer, are of great importance not only for the creation of microelectronic and spintronic devices but also to clarify the mechanisms of spin-dependent tunneling of electrons [7].…”
Section: Introductionmentioning
confidence: 99%
“…Neither of the additional layers was formed by using a typical thick‐film method; preparing the paste, screen‐printing the pattern, and firing. The layer in scheme (a)‐1 is formed of 0.2‐µm‐sized cubic MgO crystal particles and was deposited after the MgO thin film deposition . Meanwhile, those in scheme (a)‐2 and (b) are made of 12‐nm‐sized Al2O3 particles and were deposited before the deposition.…”
Section: Effect Of Space Between Ribs and Mgo Thin Filmmentioning
confidence: 99%
“…Apparently, the MgO crystal spacer layer has some advantage in lowering the discharge voltages. It is said that the MgO crystal particles have a high electron emissivity and promote low discharge voltage . In scheme (a)‐1, however, the electron emissivity of the particles has no influence by V f because there is no MgO crystal particle around the X–Y gap.…”
Section: Effect Of Space Between Ribs and Mgo Thin Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been conducted on the modeling and simulation of either the discharge characteristics for PDPs [8][9][10][11] or optical characteristics for liquid crystal displays adopting various optical films [12][13][14][15]. However, to the best of our knowledge, the modeling and simulation of the optical characteristics of PDPs, including the BRCR Simple Model of Bright-room Contrast Ratio Measurement System for … -Tae Won Beom et al performance, has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%